The Nucleus Accumbens: A Common Target in the Comorbidity of Depression and Addiction - Xu, Le; Nan, Jun; Lan, Yan (Frontiers in Neural Circuits, 2020)
The comorbidity of depression and addiction has become a serious public health issue, and the relationship between these two disorders and their potential mechanisms has attracted extensive attention. Numerous studies have suggested that depression and addiction share common mechanisms and anatomical pathways. The nucleus accumbens (NAc) has long been considered a key brain region for regulating many behaviors, especially those related to depression and addiction. In this review, we focus on the association between addiction and depression, highlighting the potential mediating role of the NAc in this comorbidity via regulation of changes in neural circuits and molecular signaling. To clarify the mechanisms underlying this association, we summarize evidence from overlapping reward neurocircuitry, the resemblance of cellular and molecular mechanisms, and common treatments. Understanding the interplay between these disorders should help guide comorbidity clinical prevention and search for a new target for comorbidity treatment.